PROYECTO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE UNA BEBIDA HIDRATANTE DE CONCENTRADO DE MARACUYÁ, EN LA CIUDAD DE LOJA - Condoy Robles, Victor Alonzo (2016)
This research paper called PROJECT FEASIBILITY FOR CREATING A COMPANY PRODUCER AND MARKETER OF A MOISTURIZING DRINK OF PASSION FRUIT CONCENTRATE was held in the province of Loja - Loja Canton, whose main objective is:  Determine the feasibility of creating a producer and marketer of sports drink concentrate of fruit in the city of Loja company. The fulfillment of this goal was made possible by the market research and marketing of the product in Loja Canton. The results of the market study served as guidelines to guide the products according to customer requirements, also the technical study allowed us to determine the optimal location thereof, the administrative study allowed us to determine the human talent needed for the project, and finally The financial study discloses the total investment of $ 45,355.45 that it will feature its own capital 55.90% and 44.10% foreign equity and financial indicators which determine the feasibility of it was calculated. The project has a capacity utilization of 80% of installed capacity for a total of 216,320 liters of concentrated passion fruit annually, with an annual increase of 5% last year reaching life to 95% of installed capacity, Total costs for the first year will be $ 211,695.89 which determines a unit cost of $ 1.22 per liter of concentrated passion fruit, with a profit margin of 25% which gives a total income of $ 264,619.86, the balance point for the first year depending on the 5 installed capacity will be at 46.46%, and in terms of sales will be $ 122,930 cents. The NAV will be worth $ 71,603.54, the IRR is 59.59% in the capital recovery period will be one year 8 months and 1 day in the cost benefit worth 0.25 cents is obtained for every dollar invested, the sensitivity analysis shows that the project supports 16% increase in costs and 12.80% on the decline in revenue. As said before it is shown that the implementation of the investment project is feasible.